Interpenetrating polymer networks: So happy together? - Silverstein, Michael S. (Polymer (Guilford), 2020)
A typical description of interpenetrating polymer networks (IPN) can be surprisingly simple, systems that consist of two crosslinked polymer networks that are physically entangled but not chemically linked. That simplistic description, however, successfully encompasses a wide range of synthesis processes and macromolecular architectures that can include “semi-IPN” (IPN-like systems containing only one crosslinked polymer) and interconnected polymer networks (IPN-like systems that also include a limited amount of inter-network chemical links). The macromolecular topologies of these systems combine kinetically entrapped molecular-level mixing with limited phase separation into a continuous range of nanodomain compositions. This perspective-review presents the family of IPN systems, describes the synthesis parameters used to generate a variety of macromolecular topologies, and discusses the damping properties, the ability to process latex IPN, the mechanical robustness of double network hydrogels, and IPN as templates for porous polymers, as well as recent innovations and cutting-edge applications. The wide gamut of macromolecular topological options described herein will serve as a guide to realizing synergistic behaviors by combining polymers in IPN-like structures. [Display omitted] •IPN macromolecular topology: two interpenetrating, but not linked, polymer networks.•IPN: entrapped molecular mixing + nanodomains with a continuous range of compositions.•IPN, semi-IPN, latex IPN, interconnected and double networks, IPN-templated porosity.•LIPN processability: phase-separated, strength-forming interparticle nanodomains.•Tuning: sequence, reaction, crosslinking, compatibility, composition, hydrophilicity.